2012
DOI: 10.1074/jbc.m111.307678
|View full text |Cite
|
Sign up to set email alerts
|

TRIM67 Protein Negatively Regulates Ras Activity through Degradation of 80K-H and Induces Neuritogenesis

Abstract: Background: TRIM67, which is selectively expressed in the cerebellum, is a novel member of the TRIM protein family. Results: TRIM67 interacts with PRG-1 and 80K-H, which is involved in the Ras-mediated signaling pathway. Conclusion: TRIM67 regulates Ras signaling via degradation of 80K-H, leading to neural differentiation including neuritogenesis. Significance: Analysis of TRIM67 would provide therapeutic benefits for neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…In the adult brain, TRIM67 was enriched in Purkinje cells of the cerebellum, and was evident in layers 2 and 3 of the cortex ( Fig.2E), cortical axon tracts passing through the caudate putamen (CPu), and scattered cells within the midbrain (Fig.3D,E, arrowheads), but TRIM67 was not detected in the hippocampus (Fig.3F). Although TRIM67 was detected in most regions of the adult and embryonic brain, it was not detected in other tested tissues ( Fig.2F) consistent with a previous report (Yaguchi et al, 2012). Compatible with immunohistochemistry, TRIM67 protein levels in the embryo were high in the cortex, whereas in the adult brain they were high in the cerebellum.…”
Section: Generation Of Trim67 -/-Micesupporting
confidence: 91%
See 1 more Smart Citation
“…In the adult brain, TRIM67 was enriched in Purkinje cells of the cerebellum, and was evident in layers 2 and 3 of the cortex ( Fig.2E), cortical axon tracts passing through the caudate putamen (CPu), and scattered cells within the midbrain (Fig.3D,E, arrowheads), but TRIM67 was not detected in the hippocampus (Fig.3F). Although TRIM67 was detected in most regions of the adult and embryonic brain, it was not detected in other tested tissues ( Fig.2F) consistent with a previous report (Yaguchi et al, 2012). Compatible with immunohistochemistry, TRIM67 protein levels in the embryo were high in the cortex, whereas in the adult brain they were high in the cerebellum.…”
Section: Generation Of Trim67 -/-Micesupporting
confidence: 91%
“…Trim9 deletion is also associated with aberrant migration, morphogenesis, and synapse organization of adult-born neurons in the murine dentate gyrus, and severe deficits in spatial learning and memory (Winkle et al, 2016). A single study has shown that TRIM67 is expressed in the mouse and human brain and regulates neuritogenesis in a mouse neuroblastoma cell line (Yaguchi et al, 2012), although its role in neurons and in vivo is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Immunostaining of Trim67 −/− mouse brain confirmed these observations. TRIM67 is abundantly expressed in the cerebellum of both mouse and human [6,11], and immunostaining with patient CSF herein showed a similar pattern.…”
Section: Discussionmentioning
confidence: 64%
“…TRIM9 and TRIM67 have both been implicated in the morphogenesis of developing neurons or neuron-like cells [5,8,11]. To investigate a potential pathogenic mechanism and examine whether Abs affect TRIM-dependent neuronal morphogenesis, the effect of patient CSF on developing murine cortical neurons was studied in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Immunoblot analysis was performed as reported previously 45 . Mutated rat BSN cDNA (c.11623C > G, p.Pro3875Ala) (BSN[Mut]), which corresponds to the mutation (c.11596C > G, p.Pro3866Ala) found in the Japanese family with PSP-like syndrome, was constructed with a QuikChange mutagenesis kit using KOD-plus-neo (KOD-401; TOYOBO) (see Supplementary Table S5).…”
Section: Genetic Methodsmentioning
confidence: 99%